2021
DOI: 10.1038/s41467-021-24103-x
|View full text |Cite
|
Sign up to set email alerts
|

Proton gradients from light-harvesting E. coli control DNA assemblies for synthetic cells

Abstract: Bottom-up and top-down approaches to synthetic biology each employ distinct methodologies with the common aim to harness living systems. Here, we realize a strategic merger of both approaches to convert light into proton gradients for the actuation of synthetic cellular systems. We genetically engineer E. coli to overexpress the light-driven inward-directed proton pump xenorhodopsin and encapsulate them in artificial cell-sized compartments. Exposing the compartments to light-dark cycles, we reversibly switch … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…By changing the amount of cholesterol-tagged DNA at the GUV periphery, we tune the degree of DNA cortex-like network formation (Figure f and Figure S24). The degree of DNA cortex-like structure formation can be quantified by the ratio of the DNA filament intensity on the membrane, I peri , over the filament intensity in the GUV lumen, I in . Cortex-like network formation is enhanced at higher concentrations of chol-DNA and saturates when the chol-DNA is supplied at a ratio of 1:1 compared to the DNA tiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By changing the amount of cholesterol-tagged DNA at the GUV periphery, we tune the degree of DNA cortex-like network formation (Figure f and Figure S24). The degree of DNA cortex-like structure formation can be quantified by the ratio of the DNA filament intensity on the membrane, I peri , over the filament intensity in the GUV lumen, I in . Cortex-like network formation is enhanced at higher concentrations of chol-DNA and saturates when the chol-DNA is supplied at a ratio of 1:1 compared to the DNA tiles.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, GUVs were deformed externally with multilayer DNA origami structures only. However, it remained unclear whether DNA filaments, or DNA tile structures, in general, are sufficiently rigid to deform membranes. Furthermore, it was unclear whether deformation can be achieved from within the GUV, where the confined volume limits the amount of DNA that is available for membrane attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, DNA nanotechnology has allowed to combine programmable molecular architectures with extrinsically controlled functions ( Bazrafshan et al, 2020 ; Jahnke et al, 2020 ). In a combinatorial approach, integration of DNA nano-architectures with synthetic cells has synergized top-down and bottom-up strategies ( Jahnke et al, 2021 ). These examples demonstrate the potential for technology innovation originating from the field.…”
Section: Recent Research Directions and Bottlenecksmentioning
confidence: 99%
“…Recently, the communication between cell-sized synthetic cells and bacteria was taken to a new level by engineering light-harvesting E. coli that creates proton gradients, leading to a pH change in the environment. By linking this pH change to pH-dependent DNA-origami attachment to the synthetic cell membrane, Jahnke et al showed that synthetic cell shape change and deformation can be triggered by the proton pumping activity of E. coli [148]. Apart from compartmentalized synthetic cells, the DIB system has also been used to construct inducible gene circuits between E. coli and synthetic cells confined in droplets-in-oil [149].…”
Section: Synthetic Cell-natural Cell Communicationmentioning
confidence: 99%